PTH-063 Establishing Audit Standards for Colonic Stent Insertion will Facilitate Service Evaluation and Planning for a Rapidly Growing Service. (4th June 2013) - Cacciottolo, T M; Menzies, D; Shenoy, A; O'Riordan, D; Gooding, I
Abstract : Introduction: Self-expandable metal stent (SEM) placement is the recommended treatment option by the National Institute for Clinical Excellence (NICE) for acute colorectal obstruction in the palliative management of inoperable colorectal cancer (CRC) as well as a bridge to planned single stage surgical intervention[1]. NICE guidance recommends that centres offering this treatment modality should have teams with expertise and capacity to stent 15 people per million population per annum[2]. It does not however provide any suitable standard for audit. Methods: All colonic stents inserted between 1st January 2008 and 31st December 2011 were included. Patient characteristics, procedure related data, outcomes and survival were recorded retrospectively from health records. Results: Systematic review of 29 case series of stent insertions reported a clinical success rate of 88%, 10% stent migration rate, 4% perforation rate, 10% reobstruction rate and 1% procedure-related mortality rate[3]. These were applied as our audit standards. A total of 69 colonic stents (in 64 patients, 35 male, mean age 74.2 years) were inserted. 15 stents were inserted in 2008 and this increased steadily to 25 in 2011.The most common indication for colonic stent insertion was a malignant stricture (89.9%). There was a 98.5% technical success rate, 2.9% migration rate, 7.2% perforation rate and a 4.3% reobstruction rate within one month of the procedure. The clinical success rate, ie successful stent insertion and decompression within 96 hours, was 88.4%. 61.1% had stent insertion as a bridge to surgery. Mean survival post procedure was 200 days (range 1–779 days). The were 2 deaths as a direct consequence of the procedure (2.9%), both of which followed perforation in patients who were too frail to undergo surgery. Conclusion: We have defined and applied audit standards for colonic stent insertion. Success and complication rates at our hospital compare favourably to published rates. There is a steady increase in colonic stent insertions and in our 2011 cohort this equated to 67.6 patients per million per annum. It is likely that this number will continue to increase and endoscopy units should take this into account when planning their service provision. Audit support will be essential, and we encourage the adoption of consistent audit standards to facilitate comparison between units. Disclosure of Interest: None Declared. References: National Institute for Health and Clinical Excellence. (2004). Improving Outcomes in Colorectal Cancers. CSGCC. National Institute for Health and Clinical Excellence.(2010). Improving Outcomes in Colorectal Cancers. Manual Update. Khot et al. Systematic Review of the Safety and Efficacy of Colorectal Stents. BJS 2002(89):1096:1102